Online Learning in the Era of Pandemic: Solution or Disaster? - Dhion Meitreya Vidhiasi (SAINTARA, 2021)
The change in life continues to change quickly. The 4.0 industry has been examined, marking a development in IT, including the Internet, Big Data and Artificial Intelligence. Everyone was not distinguished from technology by the development of IT in the 21st century. Different opinions from various parties to online learning come from face-to-face shifting paradigms. This sort of learning paradigm has multiple advantages and disadvantages to reach the aim of learning itself. This study seeks to assess the perspective of learners of online learning in this context in a COVID-19 pandemic. The study focuses on students of the English conversation of Akademi Maritim Nusantara Cilacap. The instruments used are semi-structured interviews. The researcher asked the students about the Covid-19 outbreak via the WhatsApp service. The research design employed in this research was a case study. The online study is unbelievably advantageous in the heart of the pandemic. AMN Cilacap has selected the Google Classroom Service as its Learning Management System. They will receive new terminology, knowledge, and technical skills. Thus, when they graduate in the future, students will no longer have problems using their primary app for education. Online learning is more effective than offline learning for a particular objective, information, skills, and students. Combining the benefit of online and offline teaching approaches known as combined learning will help overcome the potential limitations of online learning in the professional school of AMN Cilacap. But a mix of online and offline learning, notwithstanding the volatility of online, may be the best option to maximize its worth.